Long-term forestry and climate change effects on watershed processes and salmon populations at Carnation Creek, Vancouver Island, British Columbia - Tschaplinski, Peter J.; Reid, David A.; Pike, Robin G.; Spittlehouse, David L. (Frontiers in Ecology and Evolution, 2025)
The Carnation Creek study is located in a 11.2 km2 watershed on southwestern Vancouver Island, British Columbia, in the territory of the Huu-ay-aht First Nations. It was initiated in 1970 as a case study of the effects of forestry practices on watershed biological and physical processes, stream channels, aquatic habitats, and fish populations. The project’s pre-harvest vs. post-harvest-impact observational design was intended to run for no more than 15 years, but continual and unanticipated changes in the responses of the biogeophysical aspects of the watershed to forest harvesting motivated the unprecedented long-term intensive study that continues. Now in year 55, the knowledge gained from this site is relevant not only for informing forestry legislation, regulations, and sustainable practices, but also (1) provides guidance on regenerating stand (second pass) forestry practices in coastal watersheds; (2) allows measurement of the contributions of climate variability to observed changes and the identification of mitigation options; (3) provides science-based guidance for watershed and stream channel restoration; and (4) serves as a logged but unrestored reference watershed for restoration effectiveness evaluations. Between 1976 and 1981, 41% of the watershed was harvested. A mixture of beneficial and harmful effects on juvenile coho salmon were initially observed. Between 1976 and 2004, a warmer thermal regime initially increased growth, freshwater survival, and boosted smolt production. Thermal benefits were partly counteracted by accelerated bank erosion, channel widening, loss of in-stream wood, formation of sediment wedges, and increased streambed scour and sediment transport downstream. Over the longer term, riparian-related impacts were greatly amplified and overwhelmed by the forestry-driven landslide effects that began in 1984. Landslide impacts occurring in the headwaters took more than 20 years to propagate downstream. In the absence of habitat restoration efforts, stream channel and fish habitat complexity and stability have become greatly reduced with accelerated bedload transport, deprived riparian wood input, and loss of large logjams. These delayed effects have reversed short-term, logging-related thermal benefits for coho salmon, with major declines in fry-to-smolt survival and smolt production. The results show that forestry-related impacts may take decades to fully develop and may continue to increase for decades after harvest.